Performance Evaluation of Concentrated Solar Water Heater-cum-Distillation Unit - Kapurkar, P. M.; Kurchania, A. K. (Journal of Agricultural Engineering, 2013)
Concentrated solar water heater-cum-distillation unit, having capacity of 70 l was developed. Refractive type Fresnel lens was used as solar concentrator along with a copper plate as an absorber. The developed system was tested for its technical as well as economic feasibility of solar water heating and distillation units. Overall efficiency of the solar water heater was 42.38 percent. The yield of distilled water was 4.72 kg.m-2.day-1 and efficiency of the distillation unit was 28.78 per cent. The solar water heater coupled with distillation unit performed well. Total cost of the unit was Rs.7,524. The payback period was 2 years with benefit-cost ratio of 2.64